Coverage of Information and Communication Technology News by Selected Newspapers in Tanzania - Elia, Emmanuel F; Buhomoli, Obadia Shadrack (University of Dar es Salaam Library Journal, 2021)
This study explored media coverage of Information and Communication Technology in Tanzania ' s four print media published between 2009 and 2013. Specifically, the study aimed at; assessing the trend in covering ICTs information from 2009-2013, identifying ICTs themes covered and exploring the geographic coverage of ICTs information from 2009-2013. Data were collected using informetrics method. Microsoft Excel software 2007 and content analysis were used to analyze data. Results revealed 823 articles were published on ICTs in five years. Additionally, despite variation trends in coverage, the year 2013 had highest coverage. Results showed ICTs themes related to mobile technologies were highly reported compared to others. Results indicate international news on ICTs to be highly reported compared to local news. The study concludes that there is still low coverage of ICTs information in Tanzania newspapers. It recommends increased coverage of ICTs information in media by privately owned newspapers and reporting in local language.